Randomized controlled trial of two preparations of low protein diet for patients with chronic renal failure in Dr. Kanadi Hospital, Semarang Indonesia - Rochadi, Wahyu
Background: There is no known study on the efficacy of protein diet for patients with chronic renal failure in Indonesia. A protein diet of 0.55 g/BW/day was recommended in Kariadi Hospital, Semarang. Some studies suggested protein diets of more than 0.75 g/BW/day. Objective: The objective of this study was to compare the effect of low protein diet (0.55 g/BW/day) against a protein diet (0.8 g/BW/day) using the following parameter changes of blood urea, plasma creatinine, creatinine clearance and muscle mass. Setting: Kariadi Hospital, Semarang, Indonesia. Design: A randomized controlled clinical trial. Maneuver. One hundred twenty four adult patients diagnosed with chronic renal failure based on a creatinine clearance of 5 - 75 ml/min, hospitalized in kariadi hospital, Semarang during the period august 1994 to May 1995, was randomly allocated to 2 groups, one group received a proetin diet of 0.55 g/BW/day, while another group received a protein diert of 0.8 b/BW/day. Patients were followed up for a minimum of 6 months. Compliance was assessed monthly by the validated metods of dietary intake recall. Outcome: The main outcome of this study was the mean of change of creatinine clearance. The secondary outcomes were the means of changes of blood urea, plasma creatinine and muscle mass before and after intervention. Statistical Analysis: Descriptive statistics was used to determine distribution of all variables and the pattern of outcome variables. Comparison of changes of outcome variables before and after intervention between two groups , were performed using unpaired Student's t-test. The Mann-Whitney U test was used when the variables were not normally distributed. Results: During the 18 months study period, a total of 100 patients with CRF were followed-up for 6 months. The sex distribution, age, weight, BMI, mid arm circumference, systolic and diastolic blood pressure, haemoglobine, blood urea, plasma creatinine and creatinine clearance were comparable in the 2 diet groups. Changes of creatinine clearance , blood urea and plasma creatinine were not statistically different between group A and group B. Only changes on muscle mass was found to be statistically significant. Conclusion: Low protein diet with chronic failure , decreased blood urea, plasma creatinine and increased creatinine clearance. However, the effect on changes of clearance creatinine, blood urea, plasma creatinine and muscle mass, of s 0.55 g/BW/day protein diet given for 6 months may not be significantly different from a 0.8 g/BW/day protein diet. Recommendation: For better interpretation, the researcher suggests that a similar study would be carried out, with higher number of samples, longer duration of observation and periodic blood pressure monitoring.
Thesis--(Master in Science in Biochememistry) UPCM
Keywords: Renal Failure; Low-protein diet